2021
DOI: 10.1016/j.biopsych.2020.12.033
|View full text |Cite
|
Sign up to set email alerts
|

Dysmaturation Observed as Altered Hippocampal Functional Connectivity at Rest Is Associated With the Emergence of Positive Psychotic Symptoms in Patients With 22q11 Deletion Syndrome

Abstract: observed as altered hippocampal functional connectivity at rest is associated with the emergence of positive psychotic symptoms in patients with 22q11 deletion syndrome,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 73 publications
6
18
0
Order By: Relevance
“…EC mainly holds sensory information while the hippocampus compares it with internal representations ( Falkai et al, 2000 ; Prasad et al, 2004 ). Previous studies in schizophrenia found reductions in volume of EC ( Arnold, 1999 ; Bettinardi et al, 2017 ) and higher activation in parahippocampal gyrus has been previously linked to psychosis ( Delavari et al, 2021 , Zöller et al, 2017 , Boley et al, 2014 , Friston et al, 1992 ). This finding may suggest an over-engagement in the local circuits of hippocampal complex, leading to a disruption of the novelty detection processes.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…EC mainly holds sensory information while the hippocampus compares it with internal representations ( Falkai et al, 2000 ; Prasad et al, 2004 ). Previous studies in schizophrenia found reductions in volume of EC ( Arnold, 1999 ; Bettinardi et al, 2017 ) and higher activation in parahippocampal gyrus has been previously linked to psychosis ( Delavari et al, 2021 , Zöller et al, 2017 , Boley et al, 2014 , Friston et al, 1992 ). This finding may suggest an over-engagement in the local circuits of hippocampal complex, leading to a disruption of the novelty detection processes.…”
Section: Discussionmentioning
confidence: 83%
“…Indeed, it has been already suggested that the abnormal PFC maturation in 22q11DS is driven by dopaminergic dysfunction ( Schaer et al, 2009 ). Notably, insufficient cortical dopamine combined with sub-cortical hyperdopaminergic state is one of the most accepted mechanism in psychosis ( Lodge and Grace, 2007 ) and it has been recently indicated in 22q11DS ( Delavari et al, 2021 ). In that regard, abnormally high FSD within the striatal area could be indicative of a maximal subcortical dopaminergic activation that saturates the underlying wiring structures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, hippocampal hyperactivation driven by GABAergic dysfunction has been a key finding in schizophrenia and is known to play a major role in psychosis (87, 88). In 22q11.2DS, there is growing evidence of hippocampal disruption contributing to the emergence of positive psychotic symptoms which occurs during adolescence (74, 89, 90). Notably, hippocampal-PFC connections mature during late adolescence whereas BLA-PFC connections mature during pre-adolescence (91, 92).…”
Section: Discussionmentioning
confidence: 99%
“…To optimally investigate the longitudinal changes of maturation in amygdala subdivision connectivity patterns, we employed the partial least squares correlation (PLS-C) (73) via the MATLAB-based publicly available toolbox (https://github.com/MIPLabCH/myPLS). As described in our previous publication (74), we defined the design variables to take into account the longitudinal aspect of brain maturation. In brief, a set of design variables (Y) that are chosen to encode diagnosis (22q11.2DS vs HC or PS (+) vs PS(-) or ITS(+) vs ITS(-)), longitudinal and cross-sectional age, and their interactions are included in one side.…”
Section: Methodsmentioning
confidence: 99%